2013
DOI: 10.1126/science.1235970
|View full text |Cite
|
Sign up to set email alerts
|

Control of Ribosomal Subunit Rotation by Elongation Factor G

Abstract: Protein synthesis by the ribosome requires the translocation of transfer RNAs and messenger RNA by one codon after each peptide bond is formed, a reaction that requires ribosomal subunit rotation and is catalyzed by the guanosine triphosphatase (GTPase) elongation factor G (EF-G). We determined 3 Å resolution x-ray crystal structures of EF-G complexed with a non-hydrolyzable GTP analogue and bound to the Escherichia coli ribosome in different states of ribosomal subunit rotation. The structures reveal that EF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
218
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(247 citation statements)
references
References 70 publications
26
218
3
Order By: Relevance
“…For the mRNA to become mobile, the codon-anticodon duplex must be disrupted. This may be brought about by a conformational rearrangement of the ribosome, for example, the formation of a highly rotated chimeric intermediate similar to that formed during EF-G-catalysed translocation [24][25][26] or frameshifting 27 . Although the codonanticodon interactions are weakened, the retention of peptidyltRNA Gly in the ribosome is ensured by the interactions of the nascent peptide with the ribosome, presumably through both unspecific anchoring of the N-terminal part of gp60 emerging from the ribosome peptide exit tunnel and specific interactions of the part of nascent peptide residing in the exit tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…For the mRNA to become mobile, the codon-anticodon duplex must be disrupted. This may be brought about by a conformational rearrangement of the ribosome, for example, the formation of a highly rotated chimeric intermediate similar to that formed during EF-G-catalysed translocation [24][25][26] or frameshifting 27 . Although the codonanticodon interactions are weakened, the retention of peptidyltRNA Gly in the ribosome is ensured by the interactions of the nascent peptide with the ribosome, presumably through both unspecific anchoring of the N-terminal part of gp60 emerging from the ribosome peptide exit tunnel and specific interactions of the part of nascent peptide residing in the exit tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…Several structures of EF-G-ribosome complexes were solved by X-ray crystallography and cryo-EM, where EF-G was bound to either the nonrotated, classical state (24) or rotated, hybrid states of the ribosome (2,13,(25)(26)(27)(28). Despite significant differences in ribosome conformations in all of these structures, EF-G was found in similar configurations, with domain IV overlapping with the A site on the small ribosomal subunit.…”
mentioning
confidence: 99%
“…Bulk FRET, chemical footprinting, and single-molecule FRET experiments have shown that viomycin stabilizes the ribosome in a pretranslocation state with tRNAs in hybrid A/P and P/E configurations, rotated ribosomal subunits, and the L1 stalk in a closed conformation interacting with the P-site tRNA (11-16); this structure has been visualized by cryo-EM (17). However, a crystal structure of the viomycin-bound ribosome (18) and one single-molecule FRET study (19) have suggested stabilization of the tRNAs in the classical state.Recent crystal (18,20) and cryo-EM (17) structures of the viomycin-bound ribosome have shown that the drug binds adjacent to the ribosomal A site, in a pocket between helix 44 of the 16S rRNA in the small subunit and helix 69 of the 23S rRNA in the large subunit ( Fig. 1 B and C).…”
mentioning
confidence: 99%
“…Recent crystal (18,20) and cryo-EM (17) structures of the viomycin-bound ribosome have shown that the drug binds adjacent to the ribosomal A site, in a pocket between helix 44 of the 16S rRNA in the small subunit and helix 69 of the 23S rRNA in the large subunit ( Fig. 1 B and C).…”
mentioning
confidence: 99%